CRLBs for Location and Velocity Estimation for MIMO Radars in CES-Distributed Clutter - Rojhani, Neda; Greco, Maria Sabrina; Gini, Fulvio (Frontiers in Signal Processing, 2022)
In this paper, we investigate the problem of jointly estimating target location and velocity for widely separated multiple-input multiple-output (MIMO) radar operating in correlated non-Gaussian clutter, modeled by a Complex Elliptically Symmetric (CES) distribution. More specifically, we derive the Cramer-Rao Lower Bounds (CRLBs) when the target is modeled by the Swerling 0 model and the clutter is complex t-distributed. We thoroughly analyze the impact of the clutter correlation and spikiness to provide accurate performance estimation